Asset and Inventory Data Monitoring Application Design PT. Transmarco - Didi Kurnaedi; Erna Oktora; Irfan Nasrullah; Agung Prayoga; FX Agung Pramanto (Komunitas Dosen Indonesia, 2023)
The use of IT asset and inventory management information systems can greatly benefit businesses in managing their IT assets. The objective of this study is to develop an information system application that simplifies the management of IT assets by monitoring inventory data, tracking requests for repair, borrowing, purchase, and inventory recording of IT assets. The study was conducted at PT. Transmarco and the development of the information system application involved layout design, diagram design (including an activity diagram), and database design processes. Modular programming languages such as PHP, Sublime Text, MySQL, and CSS were used in the development process. The IT Asset and Inventory Data Monitoring Application provides information on incoming goods data, outgoing goods data, stock goods, and usage history. By implementing this application, it is expected that managing asset data and IT inventory at PT. Transmarco will become much simpler, including managing item data, item history, and stock of goods. This system will enable firm personnel to efficiently manage IT assets according to the desired outcomes. Overall, the development of the IT asset and inventory data monitoring application at PT. Transmarco showcases the potential benefits of IT asset and inventory management information systems for businesses. The streamlining of IT asset management processes can result in improved efficiency, reduced costs, and better decision-making regarding IT asset investments.